Postoperative Physical Therapy to Prevent Hospital-acquired Pneumonia in Patients Over 80 Years Undergoing Hip Fracture Surgery—A Quasi-experimental Study - Ståhl A (Dove Medical Press, 2020)
Anna Ståhl,1,2 Elisabeth Westerdahl3 1Department of Physiotherapy, Örebro University Hospital, Örebro, Sweden; 2Department of Knowledge-Driven Management, Health Care Administration, Region Örebro County, Örebro, Sweden; 3University Health Care Research Center, Faculty of Medicine and Health, Örebro University, Örebro, SwedenCorrespondence: Elisabeth WesterdahlAssociate Professor, Physiotherapist, University Health Care Research Center, Örebro University Hospital, Örebro SE-701 85, SwedenTel +46 19 602 41 49Email elisabeth.westerdahl@regionorebrolan.seBackground: Hip fracture requiring surgical fixation is a common condition with high mortality and morbidity in the geriatric population. The patients are usually frail, and vulnerable to postoperative complications and delayed recovery. Few studies have investigated physical therapy methods to prevent hospital-acquired pneumonia (HAP) after hip fracture surgery.Objective: To explore whether an intensified physical therapy regimen can prevent HAP and reduce hospital length of stay in patients aged 80 and older, following hip fracture surgery.Patients and Methods: The inclusion criterion was patients aged 80 or older who had undergone hip fracture surgery at Örebro University Hospital, Sweden during eight months in 2015– 2016 (the “physical therapy group”) (n=69). The study has a quasi-experimental design with a historical control group (n=64) who had received routine physical therapy treatment. The physical therapy group received intensified postoperative physical therapy treatment, which included daily supervised early mobilization and coached deep breathing exercises with positive expiratory pressure (PEP). The patients were instructed to take deep breaths, and then exhale through the PEP-valve in three sessions of 10 deep breaths, at least four times daily. Early mobilization to a sitting position and walking was advised as soon as possible after surgery.Results: There was a significantly lower incidence of HAP in the physical therapy group; 2/69 (3%, 95%CI: 1– 10) compared to the historical control group 13/64 (20%, 95%CI: 12– 32%) (p=0.002). Patients in the physical therapy group had a significantly shorter length of stay than the control group (10.6± 4 vs 13.4± 9 days, p=0.022).Conclusion: Intensified physical therapy treatment after hip fracture surgery may be of benefit to reduce the incidence of HAP in patients over 80 years; however, the results need to be confirmed in randomized controlled trials.Keywords: breathing exercises, hospital-acquired infection, mobilization, physical therapy, postoperative, prevention